2021
DOI: 10.1017/s0954102021000213
|View full text |Cite
|
Sign up to set email alerts
|

Lithostratigraphy, age and distribution of Eocene volcanic sequences on eastern King George Island, South Shetland Islands, Antarctica

Abstract: New mapping and dating of volcanic outcrops on the east coast of Admiralty Bay, King George Island, has demonstrated that Eocene volcanic sequences are dominant and also crop out extensively elsewhere, particularly on the eastern part of the island. The sequences can be divided into at least three formations (Hennequin, Cape Vauréal and Carruthers Cliff) together with Eocene strata at Warkocz and near Lions Rump that are currently unassigned stratigraphically. New and recently published 40Ar/39Ar ages indicate… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
18
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 12 publications
(18 citation statements)
references
References 25 publications
0
18
0
Order By: Relevance
“…While the Eocene and Oligocene rocks appear in several small outcrops in west-centre King George Island (Smellie et al, 2021a), here we show the two main exposures, which are located in Admiralty Bay and Polonez Cove (Figure 13). We have used the lithostratigraphy presented by Smellie et al (2021a), who revised the conflictive models presented by former contributions (e.g., Barton, 1965;Birkenmajer, 1981;Birkenmajer, 1982;Birkenmajer et al, 1985;Birkenmajer and Zastawniak, 1989;Smellie et al, 1984;Kraus, 2005;Panczyket al, 2009; Admiralty Bay is located in the east of King George Island (Figure 13) and its exposures are dominated by the Hennequin Formation and more recent clastic and lavas rocks. While the Hennequin Formation is constrained by basaltic andesites, andesite lavas and amygdaloidal breccias, with minor presence of rhyolites (Smellie et al, 1984), Smellie et al (2021a) suggested that these rocks, along with other Eocene strata, extensively crop out in eastern King George Island.…”
Section: Admiralty Bay and Polonez Cove Areasmentioning
confidence: 58%
See 4 more Smart Citations
“…While the Eocene and Oligocene rocks appear in several small outcrops in west-centre King George Island (Smellie et al, 2021a), here we show the two main exposures, which are located in Admiralty Bay and Polonez Cove (Figure 13). We have used the lithostratigraphy presented by Smellie et al (2021a), who revised the conflictive models presented by former contributions (e.g., Barton, 1965;Birkenmajer, 1981;Birkenmajer, 1982;Birkenmajer et al, 1985;Birkenmajer and Zastawniak, 1989;Smellie et al, 1984;Kraus, 2005;Panczyket al, 2009; Admiralty Bay is located in the east of King George Island (Figure 13) and its exposures are dominated by the Hennequin Formation and more recent clastic and lavas rocks. While the Hennequin Formation is constrained by basaltic andesites, andesite lavas and amygdaloidal breccias, with minor presence of rhyolites (Smellie et al, 1984), Smellie et al (2021a) suggested that these rocks, along with other Eocene strata, extensively crop out in eastern King George Island.…”
Section: Admiralty Bay and Polonez Cove Areasmentioning
confidence: 58%
“…Additionally, while there is a plethora of local-scale geological maps, these are mostly located near research stations and unfortunately often introduce new geological units as opposed to attempting regional correlation. The most comprehensive geological map of the South Shetland archipelago was presented in the work of Smellie et al (1984), and now after almost four decades, significant new information is available (e.g., Bastias et al, 2019;Smellie et al, 2021a;Smellie et al, 2021b;Chen et al, 2021), which we gather and present herein.…”
Section: Introductionmentioning
confidence: 95%
See 3 more Smart Citations